The Effect of Entrepreneurship Learning with Proactiveness Attitude as Mediation Variable on Entrepreneurial Intention - Isnaini, Arif; Murwani, F. Danardana; Sumanto, Agus (PT FORMOSA CENDEKIA GLOBAL, 2024)
Entrepreneurship is a significant pillar in global economic development, including in Mojokerto, where entrepreneurship is increasingly prominent among vocational high school graduates. In the local context, entrepreneurship learning in vocational high schools is expected to equip students with solid skills and attitudes toward entrepreneurship, although its implementation still faces various challenges, such as limited resources and community support. This study aims to investigate the effect of entrepreneurship learning on the entrepreneurial intentions of vocational high school students in Mojokerto. With a quantitative descriptive, explanatory approach, this study used a questionnaire to collect data that was analyzed statistically. The results showed that entrepreneurship learning positively and significantly affects entrepreneurial intentions, both directly and through students' proactive attitudes. This study also considers local factors such as the economic, social, and cultural conditions of Mojokerto to provide recommendations for strategies to improve entrepreneurship learning that are more appropriate to the local context